2010
DOI: 10.1007/s00414-010-0487-8
|View full text |Cite
|
Sign up to set email alerts
|

Genus identification of toxic plant by real-time PCR

Abstract: Some plants have toxicities that are dangerous for humans. In the case of poisoning by toxic plants, a rapid and easy screening test is required for accurate medical treatment or forensic investigation. In this study, we designed specific primer pairs for identification of toxic plants, such as subgenus Aconitum, genus Ricinus, genus Illicium, and genus Scopolia, by internal transcribed spacer sequences of nuclear ribosomal DNA. Allied species of target plants, foods, and human DNA were not detected, but each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The DNA templates at 10 ng, 1 ng, 100 pg, 10 pg, and 1 pg showed successful amplification (6.8 ± 0.2, 8.0 ± 0.3, 8.9 ± 0.2, 10.3 ± 0.4, and 11.9 ± 0.3 min); however, amplification was not detected using 100 fg of DNA template. The sensitivity of the LAMP assay was higher than the previously reported sensitivity of real-time PCR (100 pg) [14]. We also confirmed that amplification of no-template controls did not occur for 20 min.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The DNA templates at 10 ng, 1 ng, 100 pg, 10 pg, and 1 pg showed successful amplification (6.8 ± 0.2, 8.0 ± 0.3, 8.9 ± 0.2, 10.3 ± 0.4, and 11.9 ± 0.3 min); however, amplification was not detected using 100 fg of DNA template. The sensitivity of the LAMP assay was higher than the previously reported sensitivity of real-time PCR (100 pg) [14]. We also confirmed that amplification of no-template controls did not occur for 20 min.…”
Section: Resultssupporting
confidence: 83%
“…Toxic plants can be identified by morphological analysis or chemical analysis using high-performance liquid chromatography (HPLC) or liquid chromatography-mass spectrometry (LC/MS) [6, 911, 13]. Recently, DNA-based analytical methods, such as real time polymerase chain reaction (PCR), have been proposed for the detection of toxic plants, such as Aconitum plants and Veratrum album [14, 15]. However, these analytical methods require long processing time and a well-equipped laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial gastric juice was made by dissolving 2.0 g of NaCl and 3.2 g of porcine pepsin in 7.0 mL of 0.2 mol L –1 HCl. Water was added to make a total volume up to 1 L with pH of 1.2 as described by Matsuyama and Nish 21 . To make an imitation peristaltic movement, each of the grinded leaves (50 mg) was digested in 100 mL of artificial gastric juice at a 37°C in a shaking incubator at 50 r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are still issues to be considered in using DNA barcoding as a clinical diagnostic tool for rapid identification of toxic plants. (1) A study has shown that the recovery of deoxyribonucleic acid from digested target plants is lower than that of untreated samples (Matsuyama and Nishi, 2011). In our study, some samples showed difficulties in amplifying the matK region after SGF digestion.…”
Section: Prospects and Problems Of Dna Barcoding As A Useful Tool For Clinical Identificationmentioning
confidence: 54%